Citrix cloud solutions for children with special learning needs in the USA - Yu. G. Nosenko (Academy of Cognitive and Natural Sciences, 2015)
The research goal is to display the U.S. experience in the use of private Citrix clouds in teaching pupils with special educational needs: students who, are threatened to leave studying because of social circumstances (have to work, to take care of the child, or have problems of socialization, etc.), and students with various disabilities: autism, emotional disorders, developmental delays. Research objectives: separation of the learning process of children with special needs as a pedagogical problem; describing the perspectives of ICT use in teaching children with special needs; highlighting the experience of the United States on the use of private Citrix clouds in teaching students with special needs. Object of research: a learning process for students with special needs using cloud technologies. Subject of research: U.S. experience in using Citrix clouds in teaching students with special needs. Research methods used: descriptive (sources analysis, study of government documents). Results of the research. The U.S. law requires public schools to provide special education services to children with special needs. Since not all schools have developed enough for this infrastructure it has become common practice to attract private centers to address this problem. Recognized leader in this direction is the Educational Services of America, which uses private Citrix cloud. Thanks to cloud solutions, children with disabilities have access to instructional materials in accessible format allowing them to overcome barriers to learning, demonstrate learning achievements, to succeed. The main conclusions. The recent years are marked by significant changes in education: an increasing number of electronic resources; the learning process becomes more independent of the physical location of its subjects and of the time limits; new ways and possibilities to obtain education for children with special needs.